First Nations women clients: Experiences in dual relationships. - Badine, Terry Donna (Author); Schmidt, Glen (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2003)
No abstract available. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1231348